ECO-FRIENDLY INNOVATION: POTENTIAL OF RED DRAGON FRUIT PEEL EXTRACT IN SILVER NANOPARTICLE BIOSYNTHESIS - Dwi Puspita, Alfiana; Adhila, Ghina; Sari, Della Puspita; Wicaksono, Sigit Candra; Fahriati , Zahira (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
East Kalimantan is one of the regions that cultivates red dragon fruit (Hylocereus polyrhizus) in large quantities due to its promising health benefits. The peel of red dragon fruit has antioxidant activity comparable to its flesh, yet it is rarely utilized and often discarded as organic waste. This study aims to explore the potential of water and ethanol extracts from red dragon fruit peel as antioxidant sources that can serve as natural reducing and stabilizing agents in the biosynthesis of silver nanoparticles (AgNPs). Extraction using water and ethanol solvents was conducted to analyze the antioxidant compounds in the peel. The extract with the strongest antioxidant activity was used for AgNP biosynthesis, and the absorption peak was observed using UV-Vis spectrophotometry at a specific wavelength of 400–450 nm, which is characteristic of AgNP surface plasmon resonance. The results showed that the ethanol extract exhibited stronger antioxidant potential based on its lower IC₅₀ value and functioned effectively as a reducing and stabilizing agent at synthesis temperatures of 40–50°C, without degrading the extract's secondary metabolites. These findings support the utilization of red dragon fruit peel as a sustainable and eco-friendly raw material for the development of health-related products.